Interrelationships between electrical, mechanical and hydration properties of cortical bone. (January 2018) - Unal, Mustafa; Cingoz, Fatih; Bagcioglu, Cevat; Sozer, Yilmaz; Akkus, Ozan
Abstract: Interrelationship between electrical and mechanical properties of cortical bone and the role of bone composition in this interrelationship are not comprehensively investigated to date. This study aimed to investigate associations of electrical properties (i.e., specific impedance, dielectric constant, and conductivity) with mechanical properties (i.e., toughness, strength and elastic modulus) of wet and sequentially dehydrated cortical bone. Bovine cortical bone samples (N = 24) were subjected to three-point bending test. A sequential heat treatment protocol ensued to tease out contributions of unbound water and bound water. Demineralization was performed to understand contributions of organic matrix and the mineral phase to the electrical properties of cortical bone. Raman-spectroscopy based water measurement was used to investigate involvement of collagen- and mineral-bound water in the electrical properties. Our results showed statistically significant correlations between electrical and mechanical properties of cortical bone. Toughness and ultimate strength were negatively correlated with impedance and positively correlated with conductivity and dielectric constant. The highest correlations between electrical and mechanical properties of cortical bone were typically found at the frequencies of 0.2, 0.5 and 1 MHz. The electrical properties of bone changed significantly as a result of sequential dehydration, indicating that unbound and bound water compartments are the key determinants of the electrical properties. Comparison of porosity matched bone samples with high and low amount of bound water showed that bound water compartments may have an independent role in determining electrical properties of cortical bone. Furthermore, the results indicated that collagen and mineral-bound water may contribute differentially to the electrical properties of a bone. In the overall, our results suggest that electrical properties of cortical bone may be used to assess bone toughness and strength, and also underline the necessity for developing techniques to measure these electrical properties in vivo.